RESEARCH OF FACTORS AFFECTING THE QUALITY OF DRINKS PREPARED FROM COFFEE BEANS - Arkadiy Andreevich Koksharov; Natalya Gennadievna Kostina; Rosa Zavdatovna Grigorieva (Современная наука и инновации)
Experts in the field of Economics and statistics note that coffee and drinks on its basis are the most popular and their consumption is at a consistently high level, which indicates the successful development of the coffee business in Russia.